How can we get beyond the Transformative Agreements: a Swedish perspective - Wilhelm Widmark (Revista Española de Documentación Científica)
In this work there will be a critical discussion about transformative agreements and their development. Will they lead to a rapid change towards a fully equitable open scholarly publication system or are they just a new business model for the commercial publishers that won´t drive the necessary change in the system? The article will be based on a discussion on the policy development on Open Access in Sweden, from Council conclusions to National guidelines on Open Science, and how Sweden is striving to get from policy to practice. Finally, the article will describe how the Swedish Bibsam consortia are implementing the policy developments in their strategies and how they actually negotiate to get beyond the transformative agreements.